In Silico Analysis of Sponges Compound Against Mpro COVID-19: A Review - Lianingsih, Fitri (Proceeding International Conference on Science and Engineering, 2021)
Abstract. The novel coronavirus 2019 (COVID-19) is one of the viruses that can infect humans and cause high mortality worldwide. The protease (Mpro) is a key 2019-nCoV enzyme mediate viral replication and transcription. Mpro is currently used as the candidate for the COVID-19 vaccine but yet the interaction of the protein is to be determined. The Mpro can be a target protein to design the drug of COVID19. The drug design from natural products that are considered to have low toxicity is needed against the virus. The aim of this study to determine the potential of some marine compounds against COVID-19 in silico and to find the potential amino acid residues between interaction ligandprotein receptors. The methods of this study use virtual screening of Autodock Vina and study literature to find the action mechanism between ligand and protein receptors. The result of this study was the selected marine compound which may have the potential for 2019-nCoV to be future drugs. The interaction between the best ligand-protein predominant by glutamine and threonine amino acid. The role of glutamine as immune nutrition for recovery patients for some disease and maintain the body back to the homeostasis. Threonine could contribute to inflammatory responses against foreign substances.